Horizontally polarized omnidirectional antenna using octagonal dipole array for digital television reception - Osklang, Pracha; Luadang, Bancha; Phongcharoenpanich, Chuwong; Lamultree, Suthasinee (My University, 2015)
This paper presents a horizontally polarized omnidirectional antenna using octagonal dipole array for digital television reception. The proposed antenna consists of stacked octagonal dipole array that is designed from brass sheet. The parametric study is carried out for different dimensions of distance between octagonal dipole, dipole arm and radiator to improve the impedance bandwidth. Obvious that the results show good impedance matching of S11better than 10 dB, and antenna gain of 1.1 dBi-2.3 dBi along the frequency range from 470 MHz to 862 MHz.
Keywords: DTV; horizontal polarization; omnidirectional pattern; stacked antenna; UHF antenna